Associations between healthcare worker participation in workplace wellness activities and job satisfaction, occupational stress and burnout: a cross-sectional study in Botswana - Ledikwe, Jenny H (BMJ Open, 2018)
OBJECTIVES: Healthcare workers (HWs) are prone to high levels of stress and burnout, particularly when caring for people with HIV/AIDS. This study assessed whether participation in Botswana’s Workplace Wellness Programme (WWP) for HWs was associated with job satisfaction, occupational stress, well-being and burnout. METHODS: Using multistage sampling, a paper-based questionnaire was distributed to 1856 randomly selected HWs at 135 public facilities across Botswana. Well-validated scales assessed key outcomes. Analysis of covariance models were built for psychosocial factors associated with WWP participation, controlling for associated demographics. RESULTS: Response rate was 73% (n=1348). The majority of respondents were female (62%), not married (65%) and had children (84%). Mean age was 40.0 years (SD±9.9). Respondents were roughly split between participation in no WWP activities (29.4%), 1–6 WWP activities (38.9%) and seven or more WWP activities (31.7%) in the past year. High participation was associated with older age, being a doctor or other professional, working at hospitals or District Health Management Teams, working longer in health services or working longer at a facility. In unadjusted analyses, high participation was significantly associated (P<0.05) with higher satisfaction with overall job, work, supervision, promotion, pay and professional efficacy and lower stress, exhaustion and cynicism. All associations remained significant in controlled analyses except cynicism. CONCLUSIONS: Results from this study suggest that participation in workplace wellness activities is associated with higher satisfaction with multiple job facets and lower stress, exhaustion and cynicism. Introduction of these activities may help ameliorate high occupational stress levels among HWs.